PENGARUH FRAUD HEXAGON DALAM MENDETEKSI FRAUDULENT FINANCIAL REPORTING - Nadita Saputri (2023)
This research is using a quantitative study that aims to analyze the effect of Fraud Hexagon which consists of financial stability, ineffective monitoring, change in auditors, change in directors, frequent number of CEO's pic, political connections, and state-owned enterprises on fraudulent financial reporting. The population in this study consisted of companies in the Basic Industry and Chemicals sector which listed on Indonesia Stock Exchange 2019 - 2021. The sample selection in this study used a purposive sampling method which produced 168 observations. Hypothesis testing in this study is using a panel data analysis with STATA version 14. The results of this study indicate rationalization proxied by change in auditors has a significant negative effect on fraudulent financial reporting. Meanwhile, financial stability, ineffective monitoring, change in directors, frequent number of CEO's pic, political connections and state-owned enterprises have no effect on fraudulent financial reporting.